Parameter estimation and suppression for DRFM-based interrupted sampling repeater jammer - Zhou, Chao; Liu, Quanhua; Chen, Xinliang (IET radar, sonar & navigation, 2018)
By partial interception and multiple forwarding of a radar transmitting signal, digital radio frequency memory-based interrupted sampling repeater jamming can yield a partial processing gain and form multiple false target groups in the range direction, achieving jamming effects of both suppression and deception. Various improved jamming strategies have been proposed, while jamming suppression problems have not been fully addressed. In this study, a jamming suppression method based on the idea of ‘reconstruction and cancellation’ is proposed by analysing the jamming principle. The method firstly analyses the pulse compression results with time-frequency analysis to obtain the intercepted slice number and forwarding times; then, the slice width is estimated by deconvolution processing; finally, iterative cancellation is used to suppress the jamming. Performance of the method was verified by Monte Carlo simulation. The results show that the normalised error of the slice width estimation is <5% when the jamming-to-noise ratio reaches 15 dB (after pulse compress); the cancellation method can effectively restrain the jamming by bringing an improvement of signal-to-jamming ratio >16 dB.